Indocyanine green fluorescence angiography decreases the risk of anastomotic leakage after rectal cancer surgery: a systematic review and meta-analysis - Xia, Shijun; Wu, Wenjiang; Luo, Lidan; Ma, Lijuan; Yu, Linchong; Li, Yue (Frontiers in Medicine, 2023)
Background Anastomotic leakage is a serious complication after rectal cancer resection. Intraoperative use of indocyanine green fluorescence angiography (ICGFA) can help prevent anastomotic leakage, but its use is controversial. We conducted a systematic review and meta-analysis to determine the efficacy of ICGFA in reducing anastomotic leakage. Methods Relevant data and research published until September 30, 2022, was retrieved from the PubMed, Embase, and Cochrane Library databases, and the difference in the incidence of anastomotic leakage after rectal cancer resection between ICGFA and standard treatment was compared. Results This meta-analysis included 22 studies with a total of 4,738 patients. The results showed that ICGFA use during surgery decreased the incidence of anastomotic leakage after rectal cancer surgery [risk ratio (RR) = 0.46; 95% confidence interval (95% CI), 0.39–0.56; p < 0.001]. Simultaneously, in subgroup analyses for different regions, ICGFA was found to be used to reduce the incidence of anastomotic leakage after rectal cancer surgery in Asia (RR = 0.33; 95% CI, 0.23–0.48; p < 0.00001) and Europe (RR = 0.38; 95% CI, 0.27–0.53; p < 0.00001) but not in North America (RR = 0.72; 95% CI, 0.40–1.29; p = 0.27). Regarding different levels of anastomotic leakage, ICGFA reduced the incidence of postoperative type A anastomotic leakage (RR = 0.25; 95% CI, 0.14–0.44; p < 0.00001) but did not reduce the incidence of type B (RR = 0.70; 95% CI, 0.38–1.31; p = 0.27) and type C (RR = 0.97; 95% CI, 0.51–1.97; p = 0.93) anastomotic leakages. Conclusion ICGFA has been linked to a reduction in anastomotic leakage after rectal cancer resection. However, multicenter randomized controlled trials with larger sample sizes are required for further validation.